PENGARUH AIR FUEL RATIO (AFR) TERHADAP EFISIENSI TURBIN GAS PADA PLTGU UNIT 2 PT. PLN (PERSERO) KERAMASAN PALEMBANG-PROVINSI SUMATERA SELATAN - Angky Puspawan; Rifki Sulthan; Agus Suandi; Yovan Witanto (Teknosia, 2023)
Gas turbine efficiency is an indicator to determine the performance of a generator. The greater the efficiency value of the gas turbine in a generator, the better the performance of the generator. One of the things that affect the value of the efficiency of a gas turbine is the air fuel ratio. Air Fuel Ratio (AFR) is the ratio of the amount of air and fuel in the combustion process in units of mass or volume. Air fuel ratio is a factor that affects the perfection of the combustion process in the combustion chamber. In the graphic image it can be seen that the lowest AFR values ​​are on July 3 and 4 2022, when the gas turbine produces a loading of 20900 kW and 20100 kW with an AFR value of 39.76 unitless each. Whereas the highest AFR value is on June 28 2022 when the gas turbine produces a loading of 20780 kW with an AFR value of 40.68 unitless. The highest gas turbine efficiency value is on June 30, 2022, at a loading of 20,650 kW with a gas turbine efficiency of 83.3%. The lowest efficiency value is on July 2, 2022, at a load of 20,800 kW with a gas turbine efficiency of 81.05%. From the results of existing data processing and graphs, it can be seen that the value of the air fuel ratio and the efficiency of the gas turbine are inversely proportional, which means that when the value of the air fuel ratio decreases, the value of the efficiency of the gas turbine tends to increase. However, there are some deviations when the value of the air fuel ratio decreases, the efficiency of the gas turbine also decreases. Therefore it can be concluded that the value of the air fuel ratio affects the value of the efficiency of the gas turbine, however, the value of the air fuel ratio is not the only factor that affects the value of the efficiency of the gas turbine.